Impact of Alcoholism and Drug Abuse on Youths’ Personality: Understanding the Impact of Alcoholism and Drug Abuse on Youth's Personality and Society (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Alcoholism, drug abuse and dependency are a global problem and almost every Country and society is concerned with it. This abuse has killed more people, sent more victims to hospital generate more police arrest, broken up more marriages and homes. In India too alcohol is common among different sections, generally among the Poor (Mahadalils) and among the people of higher status. Atrocity on women is a corollary of alcoholism. Several cases of assault on women by the drunken husbands are reported every day in different corners of the country even causing death. Psychological and interpersonal factors play major role in developing dependency on alcohol. It has been found that there are some alcoholic personalities such persons tend to be more emotionally immature. The present study confirms that introversion and neuroticism serve as major factors of alcoholism.